Evaluación de viabilidad para la integración de energía solar a la matriz de una vivienda unifamiliar en la ciudad de Bogotá (2024)
This study evaluates the feasibility of integrating a photovoltaic system into the energy matrix of a single-family home in the city of Bogotá. The growing demand for sustainable energy sources has driven the search for alternatives to reduce dependence on conventional sources, and solar energy is then presented as a promising option in this regard. In this research, an analysis of the geographic location of the home was carried out, considering factors such as radiation and solar brightness as fundamental parameters for the installation of a photovoltaic system. In addition, the costs associated with the installation and maintenance of solar panels were evaluated, as well as the possible savings in the electricity bill over time. Therefore, the results obtained indicate that the integration of solar energy into the home's matrix is ​​highly viable considering the technical and economic aspects, thus determining that the project of integrating solar energy into the home is highly feasible in the short term, with an estimated recovery of the investment in a period of 5 years.